2020
DOI: 10.3390/jnt1010006
|View full text |Cite
|
Sign up to set email alerts
|

Nanotheranostic Carbon Dots as an Emerging Platform for Cancer Therapy

Abstract: Cancer remains one of the most deadly diseases globally, but carbon-based nanomaterials have the potential to revolutionize cancer diagnosis and therapy. Advances in nanotechnology and a better understanding of tumor microenvironments have contributed to novel nanotargeting routes that may bring new hope to cancer patients. Several low-dimensional carbon-based nanomaterials have shown promising preclinical results; as such, low-dimensional carbon dots (CDs) and their derivatives are considered up-and-coming ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 194 publications
0
19
0
Order By: Relevance
“…On day 7, the lidocaine-loaded PP film, neomycin-loaded PP film, standard Band-Aid film, and neomycin-loaded PP film with mild heat group showed thicker and better healing, whereby the wound incision site was observed to be closed. In contrast, the bare PP film and dye-loaded PP film groups demonstrated inferior healing [ 35 , 36 ]. Moreover, compared with the no-heat group, the mild heat treatment group showed better and earlier recovery from the wound.…”
Section: Resultsmentioning
confidence: 99%
“…On day 7, the lidocaine-loaded PP film, neomycin-loaded PP film, standard Band-Aid film, and neomycin-loaded PP film with mild heat group showed thicker and better healing, whereby the wound incision site was observed to be closed. In contrast, the bare PP film and dye-loaded PP film groups demonstrated inferior healing [ 35 , 36 ]. Moreover, compared with the no-heat group, the mild heat treatment group showed better and earlier recovery from the wound.…”
Section: Resultsmentioning
confidence: 99%
“…CDs showed strong absorbance in the 280-360 nm UV region with tail extending into visible region where absorption band are assigned to n-π * transition of C=O/C=N bond or π-π * transition of C=C bond [37,38]. The absorption band and emission properties of CDs can be regulated by types and content of surface modifications or surface functional groups, π-conjugated domains or variation of oxygen/nitrogen content in carbon core.…”
Section: Absorptionmentioning
confidence: 99%
“…However, the unique polymeric properties of CPDs nanomaterials make them well-suited for the different biomedical fields. Recent studies have shown that CPDs are potential candidates in biomedical sciences, both as nanocarriers and nanotransducers [43][44][45][46]. CPDs are a potential candidate for the researcher to develop novel functional materials.…”
Section: Biomedical and Theranostic Applications Of Carbon Polymer Dots (Cpds)mentioning
confidence: 99%